Optically active plasmonic resonance in self-assembled nanostructures. (5th March 2018) - Cheng, Jiaji; Hill, Eric H.; Zheng, Yuebing; He, Tingchao; Liu, Yanjun
Abstract : The raising of induced plasmonic chirality is approaching as assembled nanostructures are evolving. Abstract : The rapid development of self-assembled plasmonic chiral nanostructures has proven its promising potential in many applications. The underlying mechanism lies in the localized surface plasmon resonance properties of plasmonic colloids with respect to induced chirality via chiral molecules or chiral geometries. In this review, we summarize recent advances in both experimental phenomena and theoretical modellings, in particular to plasmonic chirality based on geometric motives, to elucidate the underlying origin of chirogenesis so as to provide insights into this fascinating field.